Altered Functional Connectivity Density in Young Survivors of Acute Lymphoblastic Leukemia Using Resting-State fMRI - Chen, Linglong (Cancer Manag Res, 2020)
OBJECTIVE: Using functional connectivity density (FCD) mapping measured by resting-state functional magnetic resonance imaging (rs-fMRI), an ultrafast data-driven graph theory approach, we attempted to study the abnormalities in neural activity of young survivors of acute lymphoblastic leukemia (ALL) and to explore the neuropathological evidence of chemotherapy-related cognitive impairment of patients. METHODS: Twenty young survivors of ALL and 18 well-matched healthy controls (HCs) were recruited in this study. All ALL patients and healthy controls underwent rs-fMRI scans and completed neurocognitive testing. The between-group differences in short-range and long-range FCD were calculated by the option of degree centrality (DC) in MATLAB software after preprocessing. The correlations between the FCD value and each of the neurocognitive outcomes were analyzed in the ALL patients. RESULTS: The group-averaged FCD maps showed similar spatial patterns between the two groups. Compared with the HCs, ALL patients showed decreased long-range FCD in regions of the bilateral lingual gyrus, cingulate cortex, hippocampal gyrus, and right calcarine fissure. Simultaneously, decreased regions in the short-range FCD map were the bilateral lingual gyrus, cingulate cortex, parahippocampal gyrus and right calcarine fissure. Increased functional connectivity (FC) was observed between the region with decreased long-range FCD and the posterior cerebellar lobe, and decreased FC was observed between the region and the middle occipital gyrus, cuneus and lingual gyrus. Thus, there existed no brain areas with increased FCD. The decreased short-range FCD value of ALL patients was positively correlated with the score on the Digit Span Test (Forward), and the increased FC value was negatively correlated with the score on the Trail Making Test part A. CONCLUSION: Our results suggest the altered functional connectivity of young survivors of ALL in the posterior region of the brain and posterior lobe of the cerebellum. Alterations in spontaneous neuronal activity seem to parallel the neurocognitive testing, which indicates that the rs-fMRI could be used as a neuroimaging marker for neurological impairment in ALL patients.